Diagnostic biomarkers for obsessive-compulsive disorder: A reasonable quest or ignis fatuus?. (November 2020) - Fullana, Miquel A.; Abramovitch, Amitai; Via, Esther; López-Sola, Clara; Goldberg, Ximena; Reina, Nuria; Fortea, Lydia; Solanes, Aleix; Buckley, Matthew J.; Ramella-Cravaro, Valentina; Carvalho, André F.; Tortella-Feliu, Miquel; et al.
Highlights: Reports an umbrella review of potential diagnostic biomarkers in obsessive-compulsive disorder (OCD). Several biomarkers showed convincing evidence of association with OCD. None of the biomarkers seems to have diagnostic specificity. Abstract: Obsessive-compulsive disorder (OCD) has been associated with a wide range of biological and neurocognitive findings, which could assist in the search for biomarkers. We conducted an umbrella review of systematic reviews and meta-analyses to assess and grade the strength of the evidence of the association between OCD and several potential diagnostic biomarkers while controlling for several potential biases. Twenty-four systematic reviews and meta-analyses were included, comprising 352 individual studies, more than 10, 000 individuals with OCD, and covering 73 potential biomarkers. OCD was significantly associated with several neurocognitive biomarkers, with varying degrees of evidence, ranging from weak to convincing. A number of biochemical, neurophysiological, and neuroimaging biomarkers also showed statistically significant, albeit weak, associations with OCD. Analyses in unmedicated samples (123 studies) weakened the strength of the evidence for most biomarkers or rendered them non-significant. None of the biomarkers seem to have sufficient sensitivity and specificity to become a diagnostic biomarker. A more promising avenue for future biomarker research in OCD might be the prediction of clinical outcomes rather than diagnosis.